This town is on fire - Harris, Pamela N. (Quill Tree Books, an imprint of HarperCollins Publishers, 2023)
"A page-turning YA contemporary novel about a Black teenager whose life is turned upside down when her white best friend becomes the latest "Becky" on the internet, and their town is left reeling from the publicity"--